2010
DOI: 10.1021/ja101608z
|View full text |Cite
|
Sign up to set email alerts
|

19F NMR Analysis of the Antimicrobial Peptide PGLa Bound to Native Cell Membranes from Bacterial Protoplasts and Human Erythrocytes

Abstract: (19)F NMR is a unique tool to examine the structure of fluorine-labeled peptides in their native cellular environment, due to an exquisite sensitivity and lack of natural abundance background. For solid-state NMR analysis, we isolated native membranes from erythrocyte ghosts and bacterial protoplasts and prepared them as macroscopically oriented samples. They showed a high purity and quality of alignment according to (31)P NMR, and the membrane-bound antimicrobial peptide PGLa could be detected by (19)F NMR. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…CD showed that all peptides are mostly α-helical in DMPC/DMPG vesicles (Figure S1, Table 1). We have previously performed solid-state 19 F-NMR experiments in both DMPC/DMPG and in bacterial and erythrocyte membranes of several AMPs, and found the same structure and orientation of peptides in both DMPC/DMPG and in biological membranes5657, supporting the conclusion that the KIA peptides are α-helical also in biological membranes.…”
Section: Discussionsupporting
confidence: 56%
“…CD showed that all peptides are mostly α-helical in DMPC/DMPG vesicles (Figure S1, Table 1). We have previously performed solid-state 19 F-NMR experiments in both DMPC/DMPG and in bacterial and erythrocyte membranes of several AMPs, and found the same structure and orientation of peptides in both DMPC/DMPG and in biological membranes5657, supporting the conclusion that the KIA peptides are α-helical also in biological membranes.…”
Section: Discussionsupporting
confidence: 56%
“…All three helical molecules (with a length of around 20 amino acids) bind to lipid bilayers, where they can be surface-bound or obliquely immersed, depending on peptide concentration (Glaser et al, 2005; Bürck et al, 2008; Strandberg et al, 2009) and temperature (Afonin et al, 2008b). A fully inserted transmembrane state of these peptides has been associated with the formation of transient pores (Afonin et al, 2008b; Ieronimo et al, 2010). These have been shown to allow the escape of small metabolites and ions (Matsuzaki, 1998), thereby also decreasing the transmembrane proton gradient and as a result ATP generation.…”
mentioning
confidence: 99%
“…Gramicidin A and alamethicin, both of which have a predominantly hydrophobic surface when folded, are generally inserted in a transmembrane alignment . Amphiphilic helices like magainin, on the other hand, are known to reside favorably on the membrane surface and tend to insert only transiently to self‐assemble as pores . These kind of membrane interactions of natural and biomimetic peptides open the door to the possibility to fight bacteria as well as cancer cells, and is of great interest for nanochemotherapy.…”
Section: Introductionmentioning
confidence: 99%